The Influence of Online Customer Review and Social Media Influencer on Purchase Decisions for Skin1004 Serum Ampoule Products for Generation Z TikTok Users in Surabaya City - Indi Arimawasti; Sugeng Purwanto; Virginia Mandasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Indonesia's skincare industry is growing rapidly as awareness of healthy skin increases. Generation Z, as the main market, is influenced by social media such as TikTok in their consumption patterns. The rise of brand overclaims triggered a crisis of trust, making Gen Z rely more on online reviews and credible influencers. The aim of this research is to analyze the influence of online customer review and sosial media influencer on purchase decisions of Skin1004 Serum Ampoule by Generation Z TikTok users in Surabaya. Using a quantitative approach, data was collected from 108 participants with purposive sampling technique through an online questionnaire and analyzed with PLS-SEM. These research results show that Online Customer Reviews and Social Media Influencers have had a significantly positive impact on purchase decisions. Influencer credibility and expertise are dominant factors, emphasizing the importance of social validation strategies in the digital era.